Ctg(x/2)-tg(x/2)-2tg(x)=4 с объяснением пожалуйста

Ctg(x/2)-tg(x/2)-2tg(x)=4 с объяснением пожалуйста
Гость
Ответ(ы) на вопрос:
Гость
ctg(x/2) - tg(x/2) - 2*tg(x) = 4 (1+cosx)/(sinx) - (1-cosx)/(sinx) - 2 * sinx/cosx = 4 (1+cosx-1+cosx)/(sinx) - 2*sinx/cosx =4 2*(cos²x - sin²x)/(sinx*cosx)=4 2*cos(2x)/(2sinx*cosx)=2 ctg(2x)=1 2x = π/4 + πn, n ∈ Z x = π/8 + π*n/2, n ∈ Z Ответ: π/8 + π*n/2, n ∈ Z Формулы: ctg(x/2) = (1+cosx)/sinx tg(x/2) = (1-cosx)/sinx sin 2x = 2sinx*cosx cos 2x = cos²x - sin²x   ctg(x) = a x = arcctg(a) + πn, n ∈ Z
Не нашли ответ?
Ответить на вопрос
Похожие вопросы